Idiopathic Mast Cell Activation Syndrome With Associated Salicylate Intolerance - Rechenauer, Tobias; Raithel, Martin; Götze, Thomas; Siebenlist, Gregor; Rückel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, André (Frontiers in Pediatrics, 2018)
IMCAS can be a rare cause for chronic abdominal pain in children. It remains a diagnosis by exclusion that can be particularly challenging due to the vast variety of possible clinical manifestations. We present a 13-year-old boy who suffered from a multitude of unspecific complaints over a long period of time. In this case an assessment of mast cell derived metabolites and immunohistochemical analysis of bioptic specimen was worthwhile. After ruling out primary (oncologic) and secondary causes for mast cell activation, pharmacologic treatment adapted to the patient's salicylate intolerance resulted in a major relief of symptoms.